Research on the second-grade students' reading comprehension ability through fix-up options strategy implementation - Tiara Ulfah; Raudhatul Jannah (English Education Journal, 2022)
Problems in reading comprehension are usually identified when the information obtained is incongruent with the reading text. Consequently, a reading strategy is made to support the comprehension ability. This study was aimed to determine the impact of reading comprehension ability on students of SMP Pos Keadilan Peduli Ummah (Henceforth called PKPU) and their responses to the implementation of the fix-up options strategy. It focused on improving reading comprehension by identifying the main idea, summarizing, making inferences, and interpreting vocabulary. A mixed-explanatory research design was used as the method of the study. Forty-four students of PKPU junior high school's second grade were involved as samples. They were split into two groups: experimental and control. The reading test was used, with data analyzed using SPSS 20 series for quantitative analysis and questionnaires analyzed using interactive analysis for qualitative analysis.  The findings showed a significant improvement in students' reading comprehension. The dominant aspects of improvement were making inferences and interpreting vocabulary. The students' responses were positive to applying fix-up strategies to improve their reading comprehension. Thus, using the fix-up options strategy was found to help students improve their reading comprehension ability.